Proyecto para la creación de una guardería dirigida a los hijos de los empleados de la ESPOL, ubicada en el campus politécnico prosperina - Duran, Monica (2009)
This paper provides a study on the establishment of a crèche for children of employees of ESPOL whose objective is to solve the need for employees ESPOL, fathers and mothers, to have a safe place where the prime care and education of their children while they are fulfilling their daily duties in office, giving them a value-added benefits to their employees, creating loyalty, values and work quality to his work center. Thanks to great workshops, teaching methods, this nursery seeks success since the start of training a child's life. After analyzing the project determined that it is not feasible to carry out the project, the financial indicators show a negative NPV and IRR negative as a result of having a negative net cash flow projected over the 5 years. To allow this project would be necessary to set a higher price than the $ 110.62 per child, which may cover the costs incurred in managing a nursery with these characteristics. In this way, if the value of the price rises will seek another market that agrees with the price.